Microbial template-based multilevel structure particle Janus dressing and preparation method thereof

By combining multi-level structural particles based on microbial templates, combined with magnetic Chlorella biochar microspheres and ZnO nanotube arrays, Janus dressing with photothermal/zinc ion sterilization and exudate regulation capabilities was prepared, which solved the problem of limited application of microbial materials in the prior art and achieved efficient wound repair effects.

CN119818714APending Publication Date: 2025-04-15BEIHANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510022964.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Existing microbial-based wound repair materials lack the modification of microorganisms and the functional integration of material structures, limiting their application and function in Janus dressings.

Method used

Using multi-level structural particles based on microbial templates, Janus dressing with photothermal/zinc ion sterilization, exudate regulation and tissue regeneration capabilities were prepared by combining magnetic Chlorella biochar microspheres @ZnO nanotube array composite particles with hydrophobic polymers.

Benefits of technology

The excellent performance of Janus dressing in wound repair is achieved, including rapid healing, effective sterilization and controllable removal of tissue fluid, which significantly improves the efficiency and effectiveness of wound repair.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119818714A_ABST
    Figure CN119818714A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of wound repair dressings, in particular to a Janus dressing of multilevel structure particles based on a microbial template and a preparation method of the Janus dressing. The Janus dressing comprises a supporting base material and magnetic nannococcus biochar microsphere (at) ZnO nanotube arrays loaded on the surfaces of the two sides of the supporting base material. The magnetic nannochloropsis charcoal microsphere and ZnO nanotube array is a composite particle with a magnetic nannochloropsis charcoal microsphere as an inner core and a ZnO nanotube array as a shell layer, and ZnO nanotubes in the composite particle are radially arranged outside the magnetic nannochloropsis charcoal microsphere; wherein the magnetic nannococcus biochar microsphere and ZnO nanotube composite particles on the surface of one side of the supporting base material are modified with a hydrophobic polymer. The Janus dressing has excellent photo-thermal sterilization / zinc ion sterilization, tissue fluid regulation and tissue regeneration promotion capabilities, and has excellent chemical stability and structural stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of wound repair dressings, and in particular to a Janus dressing of multi-level structured particles based on a microbial template and a preparation method thereof. Background Art

[0002] The skin plays an important protective and defensive role in the human body. Wound infection and subsequent wound repair is a complex process that affects the health and safety of millions of people around the world. Wound repair involves complex processes such as antibacterial and anti-inflammatory, exudate regulation, and tissue regeneration. It is of great significance to design and manufacture new materials with enhanced properties and multifunctional integration to accelerate wound repair. Wound dressings are medical products used to cover and protect wounds, designed to promote healing and prevent infection. Their functions include protecting wounds, maintaining a moist environment, relieving pain, and promoting healing. Currently, common wound dressings include gauze dressings, film dressings, foam dressings, hydrogel dressings, alginate dressings, antibacterial dressings, functional dressings, etc.

[0003] Among them, Janus dressing is a special functional dressing with asymmetric design or dual-function or double-layer structure. One side may be designed to be hydrophobic and the other side to be hydrophilic. The special wetting properties can accelerate the removal of wound exudate from the hydrophobic side to the hydrophilic side. The hydrophobic side contacts the wound, which can keep the wound environment clean, reduce the risk of infection and inflammation, and accelerate wound healing.

[0004] Microorganisms in nature have unique advantages in terms of material structure. Bioprocessing based on microbial templates can produce different functional particles and functional materials, showing great application potential in the fields of targeted drug delivery and wound repair. At present, wound repair materials prepared based on microorganisms are mostly simple direct doping, that is, using the doped microorganisms to produce oxygen through photosynthesis for wound treatment. The applicable conditions are relatively complex and harsh, and there is a lack of modification and functional integration of microorganisms and material structures, which greatly limits their application and function in Janus dressings. Summary of the invention

[0005] 1. Technical issues to be resolved

[0006] In view of the above-mentioned shortcomings and deficiencies of the prior art, the present invention provides a Janus dressing of multi-level structured particles based on a microbial template and a preparation method thereof. The Janus dressing has good photothermal / zinc ion sterilization, exudate regulation and tissue regeneration promotion capabilities, exhibits excellent performance in wound repair, and promotes the technological progress of wound dressing medical devices.

[0007] (II) Technical solution

[0008] The specific technical solutions adopted by the present invention are as follows:

[0009] In the first aspect, the present invention provides a Janus dressing of multi-level structured particles based on a microbial template, comprising: a supporting substrate, and magnetic sphaerocephala biochar microspheres@ZnO nanotube arrays loaded on the surfaces of both sides of the supporting substrate; the magnetic sphaerocephala biochar microspheres@ZnO nanotube arrays are composite particles with magnetized sphaerocephala biochar microspheres as the core and ZnO nanotube arrays as the shell, in which each ZnO nanotube is radially arranged on the outside of the magnetic sphaerocephala biochar microspheres; wherein the magnetic sphaerocephala biochar microspheres@ZnO nanotube array composite particles on the surface of one side of the supporting substrate are modified with a hydrophobic polymer.

[0010] According to a preferred embodiment of the present invention, the hydrophobic polymer is at least one of polydimethylsiloxane PDMS, polytetrafluoroethylene PTFE, silicone rubber Silicone Rubber, polyurethane PU, polyethylene PE and polypropylene PP; preferably PDMS, which can impart hydrophobicity and low surface energy to the side after UV grafting, serving as a gas / liquid barrier, and PDMS has good biocompatibility.

[0011] In a second aspect, the present invention provides a method for preparing a Janus dressing of multi-level structured particles based on a microbial template, comprising the following steps:

[0012] S1. Preparation of magnetic algae biochar microspheres

[0013] The chlorella powder is added to the Fe3O4 aqueous dispersion, and the mixture is shaken on a shaker for 20-24 hours. After the mixture is washed with deionized water, the mixture is vacuum filtered with a filter membrane having a pore size of 0.8-1.2 μm to collect the magnetic chlorella. After low-temperature drying, the mixture is carbonized at high temperature in an argon atmosphere to obtain magnetic chlorella biochar microspheres.

[0014] S2. Preparation of magnetic algae biochar microspheres @ Zn metal composite particles

[0015] The magnetic spherical algae biochar microspheres prepared in S1 are dispersed in anhydrous ethanol to obtain a slurry, and the slurry is evenly coated on an inert plate and dried naturally; a Zn metal film is sputtered and deposited on the inert plate by a magnetron sputtering method, and then the powder on the inert plate is scraped off to obtain magnetic spherical algae biochar microspheres@Zn metal composite particles;

[0016] S3. Preparation of support substrate loaded with magnetic algae biochar microspheres@ZnO nanorod arrays

[0017] Dispersing magnetic spherical algae biochar microspheres @ Zn metal composite particles in deionized water or anhydrous ethanol to obtain a dispersion; using a dip coating method to load the magnetic spherical algae biochar microspheres @ Zn metal composite particles on the support substrate; adding soluble zinc salt and hexamethylenetetramine in a molar ratio of 1:1 to deionized water, and ultrasonically mixing to obtain a ZnO nano growth solution; immersing the support substrate in the ZnO nano growth solution, and reacting at a constant temperature of 80-90°C for 10-15h; after the reaction is completed, washing with deionized water and anhydrous ethanol, and drying to obtain a support substrate loaded with magnetic spherical algae biochar microspheres @ ZnO nanorod arrays;

[0018] S4. Preparation of support substrate loaded with magnetic algae biochar microspheres@ZnO nanotube arrays

[0019] The support substrate loaded with magnetic spherical algae biochar microspheres@Zn nanorods in S3 is immersed in a KOH solution, and an etching reaction is carried out at a constant temperature of 80-90°C for 4-13 hours; after the etching reaction, it is washed with deionized water and anhydrous ethanol, and dried to obtain a support substrate loaded with magnetic spherical algae biochar microspheres@ZnO nanotube arrays;

[0020] S5. Prepare Janus dressing

[0021] A hydrophobic polymer was grafted onto one side of the support substrate of the magnetic algae biochar microspheres@ZnO nanotube arrays prepared in S4 to prepare the Janus dressing.

[0022] According to a preferred embodiment of the present invention, in S1, after the shaking of the shaker is completed, it is washed with deionized water for 2-3 times, and then vacuum filtered with a filter membrane with a pore size of 0.8-1.2 μm for 3-5 times to collect the magnetic algae, which is then freeze-dried and carbonized and sintered at a high temperature of 300-500°C for 2-3 hours in an argon atmosphere; the algae is preferably Chlorella vulgaris, and the algae can also be replaced by other unicellular microalgae.

[0023] According to a preferred embodiment of the present invention, in S2, the inert plate is a glass plate; the slurry is evenly applied to the inert plate by spraying and naturally dried to perform magnetron sputtering Zn plating; the magnetron sputtering adopts DC sputtering, the sputtering current is 40-60mA, and the sputtering time is 5-10min.

[0024] According to a preferred embodiment of the present invention, in S3, the support substrate is loaded with magnetic algae biochar microspheres @ Zn metal composite particles in an amount of 1000-2000 μg / cm 2 ; The supporting substrate is a medical textile or a medical non-woven fabric.

[0025] According to a preferred embodiment of the present invention, in S3, the zinc ion concentration in the ZnO nano-growth solution is 30-150 mM, preferably, the zinc ion concentration in the ZnO nano-growth solution is 30-50 mM, 50-70 mM, 70-90 mM, 90-110 mM, 110-130 mM or 130-150 mM.

[0026] According to a preferred embodiment of the present invention, in S3, the soluble zinc salt is zinc nitrate or zinc chloride; zinc nitrate / zinc chloride and hexamethylenetetramine are added to deionized water at a molar ratio of 1:1, and ultrasonically mixed for 5-10 minutes to obtain a ZnO nano growth solution; the supporting substrate is immersed in the ZnO nano growth solution, and reacted at a constant temperature of 80-90°C for 10-15 hours; after the reaction is completed, it is washed with deionized water and anhydrous ethanol for 3-5 times each, and dried at 55-70°C for 6-8 hours to obtain a supporting substrate loaded with magnetic algae biochar microspheres @ ZnO nanorod arrays.

[0027] According to a preferred embodiment of the present invention, in S4, the concentration of the KOH solution is 70-110mM, preferably 70-80mM, 80-90mM, 90-100mM or 100-110mM; after the etching reaction is completed, it is washed with deionized water and anhydrous ethanol for 3-5 times each, and dried at 55-70°C for 6-8h to obtain a support substrate loaded with magnetic algae biochar microspheres @ ZnO nanotube arrays. The concentration of the KOH solution affects the ZnO nanotube structure and etching depth. During the etching reaction, the support substrate is placed at the bottom of the KOH solution.

[0028] According to a preferred embodiment of the present invention, in S5, the hydrophobic polymer is at least one of polydimethylsiloxane PDMS, polytetrafluoroethylene PTFE, silicone rubber Silicone Rubber, polyurethane PU, polyethylene PE and polypropylene PP; preferably PDMS.

[0029] According to a preferred embodiment of the present invention, in S5, PDMS and chloroform are mixed at a mass ratio of 1:5-1:20 to obtain a low-concentration PDMS solution, and the PDMS solution is sprayed (spraying distance is 30-50cm) to one side of the support substrate loaded with the magnetic spherical algae biochar microspheres @ ZnO nanotube array, and ultraviolet light is irradiated for 1-3min to graft PDMS on the surface of the magnetic spherical algae biochar microspheres @ ZnO nanotube array on one side of the support substrate. At this time, the surface of the magnetic spherical algae biochar microspheres @ ZnO nanotube array on the side surface of the support substrate is covalently bonded to PDMS, so that the outer end of the ZnO nanotube array is super-hydrophobic, and the other side surface of the support substrate is also super-hydrophilic.

[0030] Preferably, low-concentration PDMS UV grafting is used to graft the ZnO nanotubes on one side of the dressing with PDMS, and the grafted part forms a super-hydrophobic surface, the local area without PDMS grafting is still a super-hydrophilic surface, and the other side of the dressing without grafting is still a super-hydrophilic surface. Therefore, when spraying the PDMS solution, it can be sprayed according to a preset pattern, so that the PDMS grafted surface is super-hydrophobic-super-hydrophilic interlaced, and a super-hydrophilic-super-hydrophobic patterned surface on one side of the Janus dressing can be achieved.

[0031] (III) Beneficial effects

[0032] The beneficial technical effects of the present invention include the following aspects:

[0033] 1. Superparamagnetic Fe3O4 nanoparticles are deposited on the surface of coccolithophore cells, and further carbonized and sintered in an argon atmosphere to obtain magnetic coccolithophore biochar microspheres. The magnetic coccolithophore biochar microspheres are used as a forming template, and through magnetron sputtering, hydrothermal growth of nanorods and nanotube etching and other steps, composite microparticles with magnetic coccolithophore biochar microspheres as the core and regularly arranged ZnO nanotube arrays as the shell are obtained. In the process of preparing the composite microparticles, the diameter of the composite microparticles, the diameter of the ZnO nanotubes, the looseness of the ZnO nanotube array, the orderliness of the array, the structure and depth of the ZnO nanotubes can be adjusted by adjusting the magnetron sputtering current parameters, sputtering time, the concentration of the ZnO nano growth solution, the reaction time, the concentration of the etching KOH solution, the etching time and other parameters, which is conducive to the realization of the adjustable multi-level structure preparation of the composite microparticles. The raw materials for the preparation are easy to obtain and pollution-free, ensuring the safety of the Janus dressing.

[0034] 2. Based on the material and structural advantages of the biochar microspheres of spherical algae, the present invention combines the Fe3O4 nanoparticle layer with the ZnO nanotube shell layer, so that the composite particles have excellent light absorption performance and photothermal conversion ability, and show excellent photothermal performance under infrared light irradiation; further, through ultraviolet grafting of hydrophobic polymers, the super-hydrophilic-super-hydrophobic patterned surface on one side of the Janus dressing and the super-hydrophilic characteristics on the other side can be achieved. The Janus dressing of the present invention not only has excellent photothermal sterilization and zinc ion sterilization performance, but also can realize the anti-gravity pumping of droplets, thereby achieving the effect of controllable removal of wound tissue fluid.

[0035] 3. Experiments have shown that the Janus dressing provided by the present invention, when applied to the surface of infected wounds in mice, has excellent photothermal sterilization, zinc ion sterilization, anti-inflammatory and tissue regeneration properties, can significantly accelerate wound healing, and the dressing has good chemical stability. Even after wound treatment and long-term placement, the Janus dressing can still maintain good chemical stability and Janus wetting properties.

[0036] In summary, the present invention uses the magnetic biochar of sphaerocephala as a template and combines the ZnO nanotube array on its surface to prepare a composite particle with the advantages of multifunctional integration and performance enhancement, which can be loaded in different supporting substrates to form a Janus dressing. The dressing has excellent chemical stability, structural stability and wetting properties, and can promote the rapid closure and repair of infected wounds, providing a new technical idea for the design of wound repair dressings. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 The present invention is a flow chart of the method for preparing the Janus dressing.

[0038] Figure 2 Scanning electron microscope images of Chlorella biochar microspheres, magnetic Chlorella biochar microspheres, and magnetic Chlorella biochar microspheres@ZnO nanorod arrays at different reaction concentrations.

[0039] Figure 3 Scanning electron microscope images of magnetic Chlorella biochar microspheres@ZnO nanotube arrays under different KOH etching conditions.

[0040] Figure 4 Scanning electron micrographs of the original support substrate, the support substrate loaded with magnetic Chlorella biochar microspheres@ZnO nanorod arrays, and the Janus dressing loaded with magnetic Chlorella biochar microspheres@ZnO nanotube arrays.

[0041] Figure 5 The photothermal curve diagram and cyclic photothermal curve diagram of the Janus dressing of the present invention at different light power densities.

[0042] Figure 6 These are pictures of the Janus dressing of the present invention for directional blood transport in mice, pictures of different surfaces of the Janus dressing after transporting a large number of droplets, and pictures of the air permeability test of the Janus dressing.

[0043] Figure 7 The experimental treatment effect of the Janus dressing of the present invention on bacterially infected wounds; (a) is a mouse model of bacterially infected wounds, (b) and (d) are mouse wound treatment and wound repair trajectory diagrams using the Janus dressing of the present invention on different days; (c) is a bacterial smear diagram of the wound skin tissue after the mouse wound was treated with the Janus dressing of the present invention on the 3rd and 14th days. DETAILED DESCRIPTION

[0044] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below through specific implementation modes in conjunction with the accompanying drawings.

[0045] like Figure 1As shown, it is a flow chart of a preparation method of a Janus dressing of multi-level structure particles based on a microbial template of the present invention, wherein (a) is a preparation process of composite particles with magnetized Chlorella biochar microspheres as the core and ZnO nanotube arrays as the shell, which comprises: depositing Fe3O4 nanoparticles on the outside of Chlorella to obtain Chlorella coated with Fe3O4 nanoparticles on the outside, and then sintering at high temperature under anaerobic conditions to obtain Chlorella biochar C@Fe3O4 coated with Fe3O4 nanoparticles; plating a layer of metal Zn by magnetron sputtering to obtain C@Fe3O4@Zn, and then preparing a ZnO nano growth solution composed of soluble zinc salt and hexamethylenetetramine by wet chemical method, growing ZnO on the outside of Chlorella biochar under hydrothermal conditions to form ZnO nanorod array C@Fe3O4@ZnO NRs, and then etching reaction by alkaline solution to convert the ZnO nanorod array into ZnO nanotube array to obtain C@Fe3O4@ZnO NTs composite particles. In the ZnO nano-growth solution, the ammonia produced by the decomposition of hexamethylenetetramine under heating conditions increases the alkaline environment of the solution, making it easier for zinc ions to form zinc hydroxide. Under constant temperature conditions of 80-90°C, the alkaline environment accelerates the reaction rate between zinc ions and hydroxide ions, promotes the formation of zinc hydroxide, and dehydrates zinc hydroxide to form ZnO nanorods. The Zn metal layer deposited by magnetron sputtering forms ZnO crystal nuclei in hot water, providing a basis for the subsequent growth of ZnO. As the reaction time increases, more zinc ions will gather and crystallize around these crystal nuclei, gradually forming ZnO nanorod arrays. Figure 1 (b) is based on the Janus wettability principle of the hydrophilic-hydrophobic wettability characteristics of the back of the beetle and the super-hydrophobic and super-hydrophilic characteristics of the lotus leaf on one side. Inspired by this, the present invention uses a supporting substrate to load C@Fe3O4 particles on the supporting substrate, and then uses ZnO nano growth liquid under hydrothermal conditions to grow ZnO nanorod arrays on the C@Fe3O4 particle structure, and then treats the ZnO nanorod arrays to transform them into ZnO nanotube arrays by etching with an alkaline solution, so that C@Fe3O4@ZnO NTs composite particles are loaded on the supporting substrate, and finally a hydrophobic polymer (such as low-concentration PDMS) is grafted on one side of the supporting substrate to obtain a Janus dressing with a super-hydrophilic surface on one side and a super-hydrophobic surface on the other side. When grafting the hydrophobic polymer, spray grafting can also be performed according to a preset pattern, so that one side of the surface of the Janus dressing is in the form of super-hydrophilic-super-hydrophobic interlaced distribution to meet actual use requirements.

[0046] The scheme and technical effects of the present invention are further described below in conjunction with specific embodiments.

[0047] Example 1

[0048] This embodiment provides a method for preparing hierarchical structure microparticles (magnetic Chlorella biochar microspheres@ZnO nanotube arrays) based on microbial templates, which comprises the following steps:

[0049] (1) 500 mg of Chlorella powder was added to 40 mL of Fe3O4 aqueous dispersion and shaken on a shaker (150 r / min) for 24 h. After the mixture was dispersed and washed with deionized water for 3 times, vacuum filtered with a filter membrane with a pore size of 1.2 μm, and repeated 5 times. The collected magnetic Chlorella was freeze-dried and sintered at 300 °C for 2 h in an argon environment to obtain magnetic Chlorella biochar microspheres.

[0050] (2) 500 mg of magnetic Chlorella biochar microspheres were evenly dispersed in 100 mL of anhydrous ethanol, then sprayed onto a 2 cm × 3 cm glass plate and allowed to dry naturally. A Zn metal layer was then sputtered on the glass plate using a DC electromagnetic sputtering method. The current of the magnetron sputtering was 50 mA and the sputtering time was 10 min. The powder on the glass plate was scraped off and collected for later use.

[0051] (3) preparing 200 mL of a ZnO nano-growth solution containing 30 mM, 50 mM, 70 mM, 90 mM, 110 mM, 130 mM or 150 mM zinc nitrate and an equimolar amount of hexamethylenetetramine to the zinc nitrate, and ultrasonically mixing for 10 min to obtain a ZnO nano-growth solution.

[0052] The powder prepared in step (2) was put into ZnO nano growth solution, heated to 80°C in a water bath and reacted for 12 hours. After the reaction was completed, it was washed with deionized water / anhydrous ethanol for 3 times each, and dried at 60°C for 6 hours to obtain composite particles of magnetic Chlorella biochar microspheres@ZnO nanorod arrays.

[0053] (4) Prepare 200 mL of 70 mM KOH solution, add the composite particles of magnetic Chlorella biochar microspheres@ZnO nanorod arrays in step (3) into the KOH solution, heat to 90°C in a water bath and react for 12 h. After the reaction is completed, wash with deionized water / anhydrous ethanol three times each, and dry at 60°C for 6 h to obtain composite particles of magnetic Chlorella biochar microspheres@ZnO nanotube arrays.

[0054] like Figure 2 (a) shows a SEM image of Chlorella biochar microspheres, which are Chlorella biochar microspheres prepared by directly sintering Chlorella at 300°C for 2 hours in an argon environment. The surface of the Chlorella biochar microspheres is clean and has wrinkles. Figure 2 (b) shows a SEM image of the magnetic Chlorella biochar microspheres prepared in step (1) of this embodiment. The Chlorella biochar microspheres are coated with a Fe3O4 nanoparticle layer, and the surface of the Chlorella biochar is evenly loaded with magnetic nanoparticles. Figure 2 (c) is a SEM image of the magnetic Chlorella biochar microspheres@ZnO nanorod arrays prepared by heating the Zn ions and hexamethylenetetramine in the ZnO nano-growth solution in step (3) to 80°C in a water bath for 12 hours. Figure 2 (c) shows that the surface of magnetic Chlorella biochar microspheres @ ZnO nanorod array structure particles presents a regular, well-directional three-dimensional nanorod structure; and when the zinc ion concentration in the ZnO nano growth solution gradually increases from 30mM to 150mM, under the condition of constant reaction temperature and time, the ZnO nanorod array on the surface of magnetic Chlorella biochar microspheres changes from loose disorder to tight order and the diameter of the ZnO nanorods gradually increases. Therefore, when preparing a supporting substrate loaded with magnetic Chlorella biochar microspheres @ ZnO nanorod arrays, the purpose of adjusting the diameter of the ZnO nanorods and the looseness of the ZnO nanorod array can be achieved by adjusting the concentration of zinc ions in the ZnO nano growth solution.

[0055] Among them, when the zinc ion concentration in the ZnO nano-growth solution is 90 mM, the diameter distribution of the ZnO nanorods on the surface of the prepared microbial template adjustable multi-level structure particles is uniform and the arrangement is regular.

[0056] Example 2

[0057] The difference between this embodiment and embodiment 1 is only step (3) and step (4), and the remaining steps and conditions are the same as those in embodiment 1.

[0058] Step (3) of this embodiment: prepare 200 mL of ZnO nano growth solution, which contains 90 mM zinc nitrate and 90 mM hexamethylenetetramine, and mix by ultrasonic for 10 min to obtain ZnO nano growth solution. Put the powder prepared in step (2) into the ZnO nano growth solution, heat it in a water bath to 80°C for 12 h, and after the reaction is completed, wash it with deionized water / anhydrous ethanol for 3 times each, and dry it at 60°C for 6 h to obtain composite particles of magnetic Chlorella biochar microspheres@ZnO nanorod arrays.

[0059] Step (4) of this embodiment: prepare 200 mL of KOH solution with concentrations of 70 mM, 90 mM, and 110 mM, put the composite particles of magnetic Chlorella biochar microspheres @ ZnO nanorod array in step (3) into the KOH solution, heat to 90°C in a water bath and react for 4 h, 8 h, 10 h, and 12 h. After the reaction is completed, wash with deionized water / anhydrous ethanol for 3 times each, and dry at 60°C for 6 h to obtain composite particles of magnetic Chlorella biochar microspheres @ ZnO nanotube arrays.

[0060] like Figure 3The figure shows the morphology of composite microparticles prepared under different etching conditions. When the concentration of the KOH etching solution varies between 70-110 mM and the reaction time varies between 4-12 h, different degrees of etching can be achieved to obtain ZnO nanotubes and nanotube structures of different depths. When the etching time is short, only a small amount of nanotubes appear; when the KOH concentration is low, the etching is also insufficient. As the concentration of the KOH solution and the reaction time increase, the nanotubes are over-etched, some of the nanotubes dissolve, and the structural integrity is poor. Among them, Figure 3 As shown in (d), ZnO nanotubes with the best morphology can be obtained by etching at 90°C for 12 h in 70 mM KOH solution.

[0061] Example 3

[0062] This embodiment provides a method for preparing a Janus dressing of multi-level structured microparticles based on a microbial template, comprising the following steps:

[0063] (1) 500 mg of Chlorella powder was added to 40 mL of Fe3O4 aqueous dispersion and shaken on a shaker (150 r / min) for 24 h. After the mixture was dispersed and washed with deionized water for 3 times, vacuum filtered with a filter membrane with a pore size of 1.2 μm, and repeated 5 times. The collected magnetic Chlorella was freeze-dried and sintered at 300 °C for 2 h in an argon environment to obtain magnetic Chlorella biochar microspheres.

[0064] (2) 500 mg of magnetic Chlorella biochar microspheres were evenly dispersed in 100 mL of anhydrous ethanol, then sprayed onto a 2 cm × 3 cm glass plate and allowed to dry naturally. A Zn metal layer was then sputtered on the glass plate using a DC electromagnetic sputtering method. The current of the magnetron sputtering was 50 mA and the sputtering time was 10 min. The powder on the glass plate was scraped off and collected for later use.

[0065] (3) Prepare 200 mL of ZnO nano-growth solution containing 90 mM zinc nitrate and 90 mM hexamethylenetetramine, and mix them by ultrasonic mixing for 10 min to obtain the ZnO nano-growth solution.

[0066] The powder prepared in step (2) was dispersed in anhydrous ethanol, and a 3 cm × 3 cm medical PP non-woven fabric was immersed therein to allow the medical PP non-woven fabric to fully absorb the dispersion, and the ethanol was evaporated to obtain a non-woven fabric loaded with magnetic Chlorella biochar microspheres @ Zn metal composite particles, wherein the composite particle loading amount was 2000 μg / cm 2 ; The non-woven fabric was placed at the bottom of the ZnO nano-growth solution and heated to 80°C in a water bath for 12 hours. After the reaction was completed, it was washed with deionized water / anhydrous ethanol three times each and dried at 60°C for 6 hours to obtain a non-woven fabric loaded with magnetic Chlorella biochar microspheres@ZnO nanorod arrays.

[0067] (4) Prepare 200 mL of a 70 mM KOH solution, put the non-woven fabric loaded with the magnetic Chlorella biochar microspheres@ZnO nanorod array in step (3) into the KOH solution, heat to 90°C in a water bath and react for 12 h. After the reaction is completed, wash with deionized water / anhydrous ethanol three times each, and dry at 60°C for 6 h to obtain a non-woven fabric loaded with the magnetic Chlorella biochar microspheres@ZnO nanotube array.

[0068] (5) Disperse PDMS in chloroform at a mass ratio of 1:20 to obtain a PDMS solution. Spray the PDMS solution onto one side of the non-woven fabric loaded with magnetic Chlorella biochar microspheres@ZnO nanotube arrays at a spraying distance of 30 cm. After spraying, irradiate with ultraviolet light for 1 min to obtain a Janus dressing. Low-concentration PDMS UV grafting is used to graft PDMS onto the outer ends of the ZnO nanotubes on one side of the dressing surface, forming a super-hydrophobic surface at the grafted site, and the local area without PDMS grafting is still a super-hydrophilic surface. The ungrafted surface on the other side of the dressing is a super-hydrophilic surface.

[0069] like Figure 4 The following are scanning electron micrographs of the original nonwoven fabric, the nonwoven fabric loaded with magnetic Chlorella biochar microspheres@ZnO nanorod arrays, and the Janus dressing loaded with magnetic Chlorella biochar microspheres@ZnO nanotube arrays. Figure 4 As shown in (a), the original non-woven fabric has a smooth surface; as shown in (b1)-(b2), the non-woven fabric obtained by the treatment of steps (1)-(3) can be firmly bonded to the surface of the non-woven fabric fiber due to the close connection between the surface particles and the growth process of the ZnO nanorods, so that the magnetic Chlorella biochar microspheres @ ZnO nanorod array microspheres can maintain a stable morphology structure. As shown in (c1)-(c3), after the alkaline solution etching treatment in step (4), the magnetic Chlorella biochar microspheres @ ZnO nanorod arrays on the surface of the non-woven fabric are transformed into magnetic Chlorella biochar microspheres @ ZnO nanotube arrays in a 70mM KOH solution and a 90°C water bath for 12h. After the PDMS UV grafting reaction, only the surface wettability of the dressing is changed, and the micro-nano multi-level structure on its surface does not change.

[0070] Performance testing of Janus dressing

[0071] 1. The Janus dressing of this embodiment was tested for its photothermal curve and cyclic photothermal curve at different light power densities. The test results are as follows: Figure 5 shown. Figure 5 (a) shows the temperature rise and stabilization process under different power densities; Figure 5(b) shows the periodic temperature change under different power densities, and the periodic heating and cooling process. Under the synergistic effect of Chlorella biochar microspheres, Fe3O4 nanoparticle layer, and ZnO nanotube shell structure, the Janus dressing prepared in this embodiment can achieve rapid photothermal heating under 808nm infrared light. As the power density of 808nm infrared light increases (0.5, 1, 2Wcm -2 ), the photothermal temperature rise showed a positive correlation and reached the highest temperature quickly within 10 seconds. After multiple infrared light on / off cycles, the Janus dressing still maintained stable photothermal performance, achieving efficient and long-term photothermal sterilization function at the wound.

[0072] 2. The Janus dressing of this example was used for the directional blood transport and air permeability test in mice. The test results are as follows: Figure 6 As shown. Figure 6 As shown in (a), since one side of the Janus dressing is a superhydrophobic-superhydrophilic interlaced morphology, and the other side is a superhydrophilic Janus wetting property, the mouse blood droplets can achieve rapid directional transport in the positive and anti-gravity direction, that is, directional transport from the superhydrophobic side to the superhydrophilic side, which can meet the controllable removal of excess tissue fluid from the wound. Since one side of the Janus dressing has a low concentration of PDMS grafted on the surface, forming a superhydrophobic-superhydrophilic interlaced wetting property, after the first drop of liquid is transported, a "liquid channel" is formed between the superhydrophilic site on the grafted side and the superhydrophilic surface on the other side, so that the transportation time of subsequent droplets is greatly shortened after contacting the Janus dressing.

[0073] like Figure 6 As shown in (b), even after multiple directional droplet transports, whether it is water droplets or mouse blood, the superhydrophobic surface of the Janus dressing remains dry and clean, while the superhydrophilic surface is completely wetted by the liquid. This unique wetting property allows the hydrophobic and hydrophilic side of the Janus dressing to be covered on the wound during wound treatment, ensuring the cleanliness of the wound surface and controllable removal of tissue fluid during wound treatment, effectively reducing the risk of infection and the problem of excessive tissue fluid affecting wound healing.

[0074] like Figure 6 As shown in (c), steam can smoothly pass through the Janus dressing into the empty bottle above. The excellent air permeability meets the air permeability requirements of wound dressings on the skin surface.

[0075] 3. The Janus dressing of this example was used in a mouse bacterial infection wound treatment experiment. The test results are as follows: Figure 7 As shown. Figure 7(a) shows a model of bacterial-infected mouse wounds; (b) and (d) are wound images and wound repair trajectory diagrams of infected mouse wounds treated with the Janus dressing of this embodiment for 0-14 days, respectively; (c) is a bacterial smear of the wound skin tissue on the 3rd and 14th days of treatment of infected mouse wounds.

[0076] like Figure 7 As shown in (a), a circular wound with a diameter of about 8 mm was cut on the back of the mouse, and a Staphylococcus aureus infection wound model was further established. The Janus dressing of this embodiment was attached to the wound of the infected mouse, with the super-hydrophobic surface facing the wound. Combined with infrared light (808 nm, 1 W / cm 2 ) irradiation conditions for wound treatment. As shown in (b) and (d), the wound repair diagram and wound repair trajectory diagram for 0-14 days under different treatment conditions, among which the different treatment methods were divided into four groups, Group I: control group; Group II: original non-woven fabric; Group III: Janus dressing; Group IV: Janus dressing + infrared light 10min (808nm, 1W / cm 2 The results showed that the treatment method of Group IV effectively accelerated wound healing and the excess tissue fluid on the wound surface was effectively removed. On the 14th day, the wound healing rate reached 99.76%.

[0077] like Figure 7 As shown in (c), the wounds of mice on the 3rd and 14th days were cut, bacteria were extracted from the wounds, and the bacterial dispersion was plated. The results showed that group III: Janus dressing, group IV: Janus dressing + infrared light 10min (808nm, 1W / cm 2 ) under the condition of irradiation with infrared light, the bacteria in the mouse wounds were effectively reduced, proving the zinc ion antibacterial, photothermal sterilization, and controllable removal of tissue fluid of Janus dressing. Under infrared light irradiation, the bactericidal effect of Janus dressing can reach 99.99%.

[0078] It can be seen from the above experimental results that the Janus dressing of the present invention has excellent photothermal sterilization and zinc ion sterilization characteristics, and can also remove wound tissue fluid in a targeted manner, which can significantly accelerate the healing and tissue regeneration of infected wounds in mice. In addition, even after the Janus dressing is used for wound treatment and placed in long-term conditions, the Janus dressing can still maintain good structural stability and Janus wetting properties, showing great application prospects in the field of wound treatment.

[0079] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may still be modified, or some or all of the technical features therein may be replaced by equivalents. These modifications or replacements, or the technical features in the above embodiments may be combined in the manner described in the embodiments if they do not conflict with each other, and these modifications, replacements or combinations do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A Janus dressing of multi-level structured particles based on a microbial template, characterized in that: It includes a supporting substrate and magnetic spherical algae biochar microspheres @ ZnO nanotube arrays loaded on the surfaces of both sides of the supporting substrate; the magnetic spherical algae biochar microspheres @ ZnO nanotube arrays are composite particles with magnetized spherical algae biochar microspheres as the core and ZnO nanotube arrays as the shell, and each ZnO nanotube in the composite particles is radially arranged outside the magnetic spherical algae biochar microspheres; wherein the magnetic spherical algae biochar microspheres @ ZnO nanotube array composite particles on the surface of one side of the supporting substrate are modified with a hydrophobic polymer.

2. The Janus dressing according to claim 1, characterized in that The hydrophobic polymer is at least one of polydimethylsiloxane PDMS, polytetrafluoroethylene PTFE, silicone rubber Silicone Rubber, polyurethane PU, polyethylene PE and polypropylene PP.

3. A method for preparing a Janus dressing of multi-level structured microparticles based on a microbial template, characterized in that: The steps include: S1. Preparation of magnetic algae biochar microspheres Add the spherical algae powder to the Fe3O4 aqueous dispersion, shake on a shaker for 20-24 hours, wash with deionized water, and then vacuum filter with a filter membrane with a pore size of 0.8-1.2μm to collect the magnetic spherical algae. After low-temperature drying, high-temperature carbonization is performed under an argon atmosphere to obtain magnetic spherical algae biochar microspheres. S2. Preparation of magnetic algae biochar microspheres @ Zn metal composite particles The magnetic algae biochar microspheres prepared in S1 were dispersed in anhydrous ethanol to obtain a slurry, and the slurry was evenly spread on an inert plate and dried naturally; A Zn metal film is sputtered and deposited on the inert plate by a magnetron sputtering method, and then the powder on the inert plate is scraped off to obtain magnetic sphaerocephala biochar microspheres@Zn metal composite particles; S3. Preparation of support substrate loaded with magnetic algae biochar microspheres@ZnO nanorod arrays Dispersing the magnetic spherical algae biochar microspheres @ Zn metal composite particles in deionized water or anhydrous ethanol to obtain a dispersion; using a dip coating method to load the magnetic spherical algae biochar microspheres @ Zn metal composite particles on the support substrate; Add soluble zinc salt and hexamethylenetetramine to deionized water in a molar ratio of 1:1, and perform ultrasonic mixing to obtain a ZnO nano growth solution; immerse a support substrate in the ZnO nano growth solution, and react at a constant temperature of 80-90°C for 10-15 hours; after the reaction is completed, wash with deionized water and anhydrous ethanol, and dry to obtain a support substrate loaded with magnetic algae biochar microspheres@ZnO nanorod arrays; S4. Preparation of support substrate loaded with magnetic algae biochar microspheres@ZnO nanotube arrays The support substrate loaded with magnetic spherical algae biochar microspheres@ZnO nanorods in S3 is immersed in a KOH solution, and an etching reaction is carried out at a constant temperature of 80-90°C for 4-13 hours; after the etching reaction, it is washed with deionized water and anhydrous ethanol, and dried to obtain a support substrate loaded with magnetic spherical algae biochar microspheres@ZnO nanotube arrays; S5. Prepare Janus dressing A hydrophobic polymer was grafted onto one side of the support substrate of the magnetic algae biochar microspheres@ZnO nanotube arrays prepared in S4 to prepare the Janus dressing.

4. The preparation method according to claim 3, characterized in that: In S1, after the shaking of the shaker is completed, the magnetic algae are washed with deionized water for 2-3 times, and then vacuum filtered with a filter membrane with a pore size of 0.8-1.2 μm for 3-5 times to collect the magnetic algae, which are then freeze-dried and carbonized and sintered at a high temperature of 300-500°C for 2-3 hours in an argon atmosphere.

5. The preparation method according to claim 3, characterized in that: In S2, the inert plate is a glass plate; the slurry is evenly applied to the inert plate by spraying and dried naturally, so as to perform Zn plating by magnetron sputtering; the magnetron sputtering adopts DC sputtering, the sputtering current is 40-60mA, and the sputtering time is 5-10min.

6. The preparation method according to claim 3, characterized in that: In S3, the support substrate is loaded with magnetic algae biochar microspheres@Zn metal composite particles with a loading amount of 1000-2000 μg / cm 2 ; The supporting substrate is a medical textile or a medical non-woven fabric.

7. The preparation method according to claim 3, characterized in that: In S3, the zinc ion concentration in the ZnO nano-growth solution is 30-150 mM.

8. The preparation method according to claim 3, characterized in that: In S3, the soluble zinc salt is zinc nitrate or zinc chloride; zinc nitrate / zinc chloride and hexamethylenetetramine are added to deionized water at a molar ratio of 1:1, and ultrasonically mixed for 5-10 minutes to obtain a ZnO nano growth solution; the supporting substrate is immersed in the ZnO nano growth solution, and reacted at a constant temperature of 80-90°C for 10-15 hours; after the reaction is completed, it is washed with deionized water and anhydrous ethanol for 3-5 times each, and dried at 55-70°C for 6-8 hours to obtain a supporting substrate loaded with magnetic algae biochar microspheres @ ZnO nanorod arrays.

9. The preparation method according to claim 3, characterized in that: In S4, the concentration of the KOH solution is 70-110 mM; after the etching reaction is completed, the substrate is washed with deionized water and anhydrous ethanol for 3-5 times respectively, and dried at 55-70°C for 6-8 hours to obtain a supporting substrate loaded with magnetic algae biochar microspheres@ZnO nanotube arrays.

10. The preparation method according to claim 3, characterized in that: In S5, the hydrophobic polymer is at least one of polydimethylsiloxane PDMS, polytetrafluoroethylene PTFE, silicone rubber Silicone Rubber, polyurethane PU, polyethylene PE and polypropylene PP; When the hydrophobic polymer is PDMS, the operation method of step S5 is: PDMS and chloroform are mixed in a mass ratio of 1:5-1:20 to obtain a low-concentration PDMS solution, the PDMS solution is sprayed onto one side of the supporting substrate loaded with the magnetic sphaerocephala biochar microspheres @ ZnO nanotube array, and ultraviolet light is irradiated for 1-3 minutes to graft PDMS onto the surface of the magnetic sphaerocephala biochar microspheres @ ZnO nanotube array on one side of the supporting substrate.